Diagnostic tests for thyroid antibodies: A comparison of the precipitin and latex-fixation (Hyland TA ) tests. Issue 5 (September 1962) - Anderson, J. R.; Buchanan, W. W.; Goudie, R. B.; Gray, K. G.
Abstract : The clinical significance of thyroid antibodies is discussed and it is concluded that, of the antibody tests which have been extensively applied, the precipitin test is the most useful for diagnostic purposes. The recently introduced Hyland TA test is compared with the precipitin test. The TA test gives a rapid result and is slightly more sensitive, but it remains undecided whether a true positive result is always indicative of clinically important degrees of chronic thyroiditis. The TA test also gives occasional false positive results, not indicative of antibody to thyroglobulin. Furthermore, approximately 12% of precipitin-positive sera from patients with Hashimoto's disease give negative TA tests, and since these also have low titres, or are negative, in the tanned red cell haemagglutination test, the precipitin test is the only simple method of demonstrating the antibody concerned. In spite of these disadvantages, the TA test is regarded as a useful procedure, and there are advantages in using both the precipitin and TA tests together for routine diagnostic purposes. A modification is described whereby the TA test reagent may be used to titrate antibody to thyroglobulin.